"Tools" for the Development of the Inspection Activity in Archaeological Sites (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2015)
One of the acquisitions of contemporary conservation philosophy is precisely this: you don’t restore the image but the matter of the work; restoration is first and foremost the conservation of the work’s authenticity. The task of conservation is not returning to an impossible past but rather enabling the work to be handed down to the future. From this standpoint, in today’s conservation language we speak of conservation: guaranteeing through our efforts that the work entrusted to us will still be available for the future, for ourselves and the generations to come, eliminating or slowing down the causes of deterioration that endanger it so that it can be enjoyed and used. The project, "Milan Archaeology for Expo 2015. Towards a valorization of the archaeological heritage of the city", intends - respect to these theoretical and methodological - to develop processes of knowledge and planned conservation of urban archaeological areas with coordinated maintenance actions, promotion and communication of the different sites present in Milan historic centre. All this sites will be connected in a network system built for a larger project that it will increase the accessibility and enhancement.
Keywords: archaeological preservation; diagnosis; Roman age of Milan; state of risk; knowledge; maintenance